Understanding the U.S. wars in Iraq and Afghanistan / edited by Beth Bailey and Richard H. Immerman. - Bailey, Beth L., 1957-; Immerman, Richard H. (New York University Press, 2015)
Understanding the United States' wars in Iraq and Afghanistan is essential to understanding the United States in the first decade of the new millennium and beyond. These wars were pivotal to American foreign policy and international relations. They raised critical ethical and legal questions; they provoked debates over policy, strategy, and war planning; they helped to shape American domestic politics. And they highlighted a profound division among the American people: While more than two million Americans served in Iraq and Afghanistan, the vast majority of American and their families remained untouched by and frequently barely aware of the wars conducted in their name, far from American shores, in regions about which they knew little. Understanding the U.S. Wars in Iraq and Afghanistan gives us the first book-length, expert historical analysis of these wars. It examines the lessons and legacies of wars whose outcomes may not be clear for decades. -- Back cover.